Imag(in)ing the Invisible - Cameron, Elizabeth (Atlantis)

(untitled) (Mount Saint Vincent University, 2025)
This commentary politicizes the relational-technical economy of biomedicine and the future it forecasts for feminized bodies with chronic illnesses. As digital medical imaging technologies develop, visualizations of disease are becoming more sophisticated. I begin by critically considering the implications this has for feminized bodies with chronic illnesses through the example of endometriosis, a common chronic pain disease that is not well understood within the biomedical paradigm. Enhanced imaging technologies promise to illuminate previously-unknowable aspects of disease pathophysiology, but what future is such technological progress enabling, and for whom? Through a critical intersectional lens, it becomes evident that the biomedical-technological future imag(in)es particular bodies, in particular places, and towards particular, but not unfamiliar ends. Enhancing abilities to visualize disease through digital technologies within a biomedical paradigm does not require us to look differently, which may be precisely what is needed. Thus, drawing theoretically on the work of bell hooks as well as critical feminist disability studies scholarship, I kindle the fire of a critical intersectional politic that transforms biomedical-technological ways of seeing the feminized body with chronic illness. Such a politic not only offers the possibility to imagine alternate futurities, but also contributes to their tangible realization.